Elevated cadmium pollution since 1890s recorded by forest chronosequence in deglaciated region of Gongga, China. (May 2020) - Wang, Xun; Luo, Ji; Lin, Che-Jen; Wang, Dingyong; Yuan, Wei
Abstract: Ice and sediment cores, peat bogs and tree rings are useful proxy records for reconstructing historical air pollution events. However, these indirect measurements are subject to interferences caused by environmental perturbations including global climate change. Therefore, using multiple proxy records has advantages in constraining the analytical findings. In this study, we utilized the chronological record of atmospheric deposition preserved in vegetation succession ecosystems in the deglaciated region for reconstructing historical pollution events. The rate of Cd accumulation in the forest chronosequence zone was investigated in a deglaciated area of the Tibetan Plateau. The results obtained through this novel approach are consistent with the variations of Cd concentration recorded in tree-ring, showing a 4–7 times increase of atmospheric Cd deposition from the 1890s to the early 1970s followed by a decrease from the mid-1970s–2000s. The Cd pollution record indicates that elevated atmospheric Cd release occurred in regions of Southwest China and South Asia due to the rapid industrial development until 1970 followed by coordinated efforts in controlling air emissions after mid-1970s. Graphical abstract: Image 1 Highlights: Enhanced cadmium accumulation was found in glacier retreated regions. Forest chronosequence is an archive to reveal the atmospheric cadmium pollution. Rapid industrial development in Asia leads to the cadmium pollution since the 1890s.